2016
DOI: 10.1186/s12885-016-2606-5
|View full text |Cite
|
Sign up to set email alerts
|

IAP antagonists Birinapant and AT-406 efficiently synergise with either TRAIL, BRAF, or BCL-2 inhibitors to sensitise BRAFV600E colorectal tumour cells to apoptosis

Abstract: BackgroundHigh expression levels of Inhibitors of Apoptosis Proteins (IAPs) have been correlated with poor cancer prognosis and block the cell death pathway by interfering with caspase activation. SMAC-mimetics are small-molecule inhibitors of IAPs that mimic the endogenous SMAC and promote the induction of cell death by neutralizing IAPs.MethodsIn this study, anti-tumour activity of new SMAC-mimetics Birinapant and AT-406 is evaluated against colorectal adenocarcinoma cells and IAP cross-talk with either onco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(18 citation statements)
references
References 42 publications
1
17
0
Order By: Relevance
“…Although melanoma cells are largely insensitive to these mimetic drugs when used as single agents, combinations with TRAIL or TRAIL receptor agonists appear as promising [106]. Thus, the IAP antagonists Birinapant and AT-406 could sensitize BRAFV600E colorectal tumor cells for TRAIL-induced apoptosis [107].…”
Section: Discussionmentioning
confidence: 99%
“…Although melanoma cells are largely insensitive to these mimetic drugs when used as single agents, combinations with TRAIL or TRAIL receptor agonists appear as promising [106]. Thus, the IAP antagonists Birinapant and AT-406 could sensitize BRAFV600E colorectal tumor cells for TRAIL-induced apoptosis [107].…”
Section: Discussionmentioning
confidence: 99%
“…Unfortunately, in many cases antitumor drugs are not effective and they often have deleterious side effects ( Iwamoto et al, 2014 ; Li and Caeyenberghs, 2018 ). Most cancer biologists agree that there is a need for new antineoplastic therapies or cotherapies, and proapoptotic strategies seem to be promising against neoplastic diseases ( Chesi et al, 2016 ; Perimenis et al, 2016 ; Rathore et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, studies have reported the enhanced antitumor activity of chemotherapeutic agents by Smac mimetics in various malignant cells (36)(37)(38)(39)(40). Several Smac mimetics, including AT-406 (38)(39)(40)(41)(42)(43), are currently undergoing clinical trials for treatment of various cancers alone or in combination with anticancer drugs (38)(39)(40)(41)(42)(43)(44)(45)(46). Smac mimetics are reported to exhibit synergistic effect in combination with DOX and facilitate cIAP1 degradation (36)(37)(38).…”
Section: Discussionmentioning
confidence: 99%